Middle school students overestimate normative support for aggression and underestimate normative support for nonviolent problem‐solving strategies. Issue 2 (4th February 2013) - Henry, David B.; Dymnicki, Allison B.; Schoeny, Michael E.; Meyer, Aleta L.; Martin, Nina C.; ,
Abstract This study tested five hypotheses related to the accuracy of students' perceptions of school norms for aggression and nonviolent problem‐solving strategies with two cohorts (ns = 852 and 968) of 6th‐grade students in 12 schools. Students consistently overestimated peer normative support for aggression and underestimated peer normative support for nonviolent problem‐solving strategies. This effect remained significant in tests of moderation by gender, ethnicity, and aggression level. Tests for moderation by the degree of provocation (e.g., if a student was hit first) and a test measuring actual norms from eighth graders and perceived norms from seventh graders suggested that the discrepancy was not due to self‐serving bias or social desirability. Longitudinal analysis found that the discrepancy remained through 8th grade. The discrepancy between actual and perceived norms has implications for risk and violence prevention, which are discussed.